Australia : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Australia. (IMF Staff Country Reports; Country Report ;, 2019)
This Article IV Consultation highlights that Australia experienced only a minor downturn after the end of the mining investment and commodity price boom but, as elsewhere, the adjustment and rebalancing has been slow, with below-target inflation and low wage growth amid economic slack. Macro-financial vulnerabilities relating to high household debt and low housing affordability have become major concerns after a recent housing boom. The baseline forecasts entail a soft landing in the housing market, but a stronger market correction remains a risk. Overall, near-term risks to growth are to the downside, mirroring the global risk picture, with the impact of shocks potentially being amplified by high household debt. The IMF staff welcomes the authorities' continued commitment to working actively with international partners to promote the global multilateral trading system. Macroeconomic policy support should remain in place until full employment and inflation in the target range are firmly within reach. The structural policy agenda appropriately targets innovation, infrastructure gaps, tax reform, and energy policy, although progress has been limited in some areas.